Infection Control In The 21st Century: Evidence, Practice, And Progress (The Review of Diabetic Studies, 2025)
BackgroundInfection control in the 21st century builds on historical foundations from pioneers like Semmelweis, Lister, and Nightingale, confronting modern threats such as healthcare-associated infections (HAIs) affecting 136 million patients annually, antimicrobial resistance (AMR) causing over 1 million deaths yearly, and challenges from urbanization, globalization, and climate change.​MethodsThis narrative review synthesizes 25 years of evidence, including landmark RCTs (e.g., REDUCE MRSA trial), meta-analyses, cohort studies, mathematical models, and GRADE/AMSTAR assessments of systematic reviews on core practices like hand hygiene, PPE, bundles, antimicrobial stewardship, and emerging technologies.​ResultsKey interventions reduced HAIs by 40-60% (e.g., chlorhexidine bathing cut MRSA by 37%, bundles lowered CLABSIs/VAP by 50-60%), with compliance rising via WHO's 5 Moments and digital tools; innovations like UV robots, RFID monitoring, and AI predictive analytics achieved 70-90% environmental reductions and outbreak forecasts; global HAI rates declined 50% since 2000, though gaps persist in LMICs and psychosocial barriers.​ConclusionsMultifaceted strategies integrating stewardship, technology (AI/nanotech), and policy yield substantial progress toward near-zero HAIs by 2030; future efforts must prioritize equity, sustained metrics, and interdisciplinary innovation to counter AMR amid evolving threats.​